Inherent differences of small airway contraction and Ca2+ oscillations in airway smooth muscle cells between BALB/c and C57BL/6 mouse strains - Zeng, Zijian; Cheng, Mengxin; Li, Meng; Wang, Tao; Wen, Fuqiang; Sanderson, Michael J.; Sneyd, James; Shen, Yongchun; Chen, Jun (Frontiers in Cell and Developmental Biology, 2023)
BALB/c and C57BL/6 mouse strains are widely used as animal model in studies of respiratory diseases, such as asthma. Asthma is characterized by airway hyperresponsiveness, which is eventually resulted from the excessive airway smooth muscle (ASM) contraction mediated by Ca2+ oscillations in ASM cells. It’s reported that BALB/c mice have inherently higher airway responsiveness, but show no different contractive response of tracheal ring as compared to C57BL/6 mice. However, whether the different airway responsiveness is due to the different extents of small airway contraction, and what’s underlying mechanism remains unknown. Here, we assess agonist-induced small airway contraction and Ca2+ oscillations in ASM cells between BALB/c and C57BL/6 mice by using precision-cut lung slice (PCLS). We found that BALB/c mice showed an intrinsically stronger extent of small airway narrowing and faster Ca2+ oscillations in ASM cells in response to agonists. These differences were associated with a higher magnitude of Ca2+ influx via store-operated Ca2+ entry (SOCE), as a result of increased expression of SOCE components (STIM1, Orai1) in the ASM cells of small airway of BALB/c mice. An established mathematical model and experimental results suggested that the increased SOC current could result in increased agonist-induced Ca2+ oscillations. Therefore, the inherently higher SOC underlies the increased Ca2+ oscillation frequency in ASM cells and stronger small airway contraction in BALB/c mice, thus higher airway responsiveness in BALB/c than C57BL/6 mouse strain.